PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) DENGAN INTERVAL PEMBERIAN AIR DAN PUPUK MAJEMUK DI TILOTE, KABUPATEN GORONTALO - Nikmah Musa; Wawan Pembengo; Nurdin Nurdin; Nursiah Oktrizqia Adri Akis (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
Lettuce (Lactuca sativa L.) is a vegetable that has high economic value and beneficial for health but in its cultivation, there are still obstacles, especially related to the plant water needs and dosage of fertilizer. This study aims to examine the growth and yield of lettuce and the interaction between water and fertilizer application time intervals in Tilote Village, Gorontalo District. This research was carried out in an acclimatization room using a randomized block design with two factors, namely the water supply interval factor (interval 2 days-A1, interval 3 days-A2) and the second factor fertilizer dosage (50 kg ha-P1, 100 kg/ha-P2). Growth parameter data (plant height, number of leaves, leaf length and leaf width) as well as plant yield (wet weight, leaf weight and percentage of leaf weight to base weight) were analyzed by ANOVA and further tested with the DMRT test at 50% level. The results showed that the water supply interval and the dosage of fertilizer has significantly affect to growth and yield of lettuce. There were an interaction between the water supply interval and the dose of fertilizer that affects the growth and yields of lettuce with the best combination were interval of 2 days and fertilizer dosage of 100 kg/ha.